Respostas cardiopulmonares durante o esforço em crianças e adolescentes nascidas prematuras - Davidson, Josy [UNIFESP] (2011)
OBJECTIVE: To describe cardiopulmonary outcomes during physical stress in prematurely born children and adolescents. DATA SOURCES: Studies were obtained from PubMed, SciELO and Lilacs in Portuguese and in English from the last 20 years. The following key-words were searched: arterial pressure, physical capacity, cardiovascular, premature, children, adolescent and pulmonary function. DATA SYNTHESIS: Prematurely born children and adolescents have airway obstruction, worse lung function and exercise capacity, more frequency of hypertension and/or higher systolic arterial pressure than those born at term. Furthermore, studies suggest that these infants have cardiovascular resistance alterations since their first days of life that could endanger the development of this system until adulthood, increasing cardiovascular risks. CONCLUSIONS: Physical stress in prematurely born individuals may lead to different cardiopulmonary outcomes compared to those born full-term. These alterations could be attributed to peculiarities of the cardiopulmonary system development.